2018
DOI: 10.1371/journal.pone.0192679
|View full text |Cite
|
Sign up to set email alerts
|

Lack of infrastructure, social and cultural factors limit physical activity among patients with type 2 diabetes in rural Sri Lanka, a qualitative study

Abstract: IntroductionSouth Asians have high prevalence of diabetes, increased cardiovascular risk and low levels of physical activity (PA). Reasons for low levels of PA have not previously been explored among Asians living within their endogenous environment. This qualitative study was performed to explore the contextual reasons that limited PA among type 2 diabetic patients living in a rural community.MethodsPurposeful sampling recruited 40 participants with long standing type 2 diabetes for this qualitative study. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 23 publications
6
21
0
Order By: Relevance
“…From the perspective of farmers, the performance of rural infrastructure construction is not very good and is inconsistent with China’s increasing infrastructure investments. This result is consistent with Arjuna and Manoj, who found that a lack of infrastructure affects rural residents’ satisfaction because of physical activity in the rural areas of Sri Lanka [ 41 ]. However, the longitudinal comparison score for farmer satisfaction was 6.1909, which was the highest among all factors investigated.…”
Section: Discussion and Suggestionssupporting
confidence: 91%
“…From the perspective of farmers, the performance of rural infrastructure construction is not very good and is inconsistent with China’s increasing infrastructure investments. This result is consistent with Arjuna and Manoj, who found that a lack of infrastructure affects rural residents’ satisfaction because of physical activity in the rural areas of Sri Lanka [ 41 ]. However, the longitudinal comparison score for farmer satisfaction was 6.1909, which was the highest among all factors investigated.…”
Section: Discussion and Suggestionssupporting
confidence: 91%
“…Despite many known benefits, older people are often reluctant to take up exercise, citing individual-level barriers such as fatigue [21], fear the movements will increase their pain [22], or simply a lack interest in exercising [23]. System level barriers such as the lack of infrastructure facilitating exercise for older people also impede uptake amongst them [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Low rates of engagement in early childhood services,36 37 distance from educational facilities and low quality of education due to infrastructural and staff qualification reasons37 are also among the reasons for not receiving quality health education. In a study conducted in rural Sri Lanka,38 lifestyle and time management as well as environmental and social factors (like social embarrassment and giving priority to household activities other than health behaviours) were reported as the factors that limited physical activity among the residents. Another study in the southwest of Iran39 showed economic and social barriers as the factors that impede the rural diabetic patients to attend in scheduled appointments.…”
Section: Discussionmentioning
confidence: 99%